Perilaku Phubbing Dengan Kualitas Persahabatan Remaja Di Pekanbaru - aiyuda, nurul; Heriandy, Tebi; Putra, Ardian Adi (Mediapsi, 2023)
The quality of friendship is a bond of relationship that is formed and has various aspects of support, conflict, and qualitative aspects of friendship that can determine how a friendly relationship can run well as it should and be able to resolve various conflicts faced. The high and low quality of friendship can be influenced by phubbing behavior. The aim of this study is to identify the relationship between phubbing behavior and the quality of friendship in Pekanbaru. This study uses quantitative methods with Pearson product moment analysis. The total sample in this study amounted to 348 respondents who were taken using quota sampling technique. Based on the results of research conducted that there is a negative relationship between phubbing behavior and the quality of adolescent friendship in Pekanbaru City with a significant value of 0.115 and a correlation coefficient of -0.463, meaning that the higher the phubbing behavior, the lower the quality of friendship, while on the contrary the lower the quality of friendship. the higher the phubbing behavior of adolescents in Pekanbaru. Therefore, the phubbing behavior of adolescent in Pekanbaru has a relationship with the quality of friendship.